Reasons for borrowing lexical unites of tourism in language standard (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The role of appearance new vocabulary in language standard is determined. The usage of tourism lexicon as the base for expressivity is analyzed. It is proved, that in touristic context lexical unites get new meaning.
Keywords: every-day lexic; touristic lexic; borrowings